Trend of Conversion into Christianity in Nepal: A Marxist Critique - Sharma, Jeewan (Journal of Rapti Babai Campus, 2026)
Nepal: 1500 years of Hindu and Buddhism, but now getting Christianity more influence This will be done by way of Marxist class relations (from their past experiences of falls or rise), caste hierarchy (of the interaction of development, globalization, and religion), unequal development and globalization history and Christian conversion as a development trend in Nepal. The study draws on reviewed academic literature, policy papers, and empirical studies referred to in this article, and some relevant writings by Nepali Marxist scholars (see, for example, Ahuti 2018; Baburam Bhattarai 2019; Chaitanya Mishra 2020). Christian conversion in Nepal is not motivated by free choice but very closely linked with caste-based discrimination, deprivation, state-resource denial and social exclusion—these are the findings of this research. Religious conversion is what marginalised groups like Dalits and poor see in Christianity: hope for equality, dignity, and social support. Also, globalisation, foreign missionary networks and liberal democratic policies have shaped the organisations to function well both spiritually and materially. Conversion seems both as a matter of faith, or identity, as well as an argument against systemic and structural oppression. To the Marxist eye, religion is the opiate of the masses, that is, it can offer the comfort of the homeopathic remedy for suffering, however, it can also be a locus of oppositional force to institutional power relations. Religious conversion is what marginalized groups like Dalits and poor see in Christianity: hope for equality, dignity, and social support. Also, globalisation, foreign missionary networks and liberal democratic policies have shaped the organizations to function well both spiritually and materially. Conversion seems both as a matter of faith, or identity, as well as an argument against systemic and structural oppression. To the Marxist eye, religion is the opiate of the masses, that is, it can offer the comfort of the homeopathic remedy for suffering, however, it can also be a locus of oppositional force to institutional power relations.